2011
DOI: 10.1111/j.1478-3231.2010.02424.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mononuclear cell therapy for patients with cirrhosis: a Phase 1 study

Abstract: BMMCs infusion is feasible and practical in a clinical setting. In vivo tracking of labelled cells demonstrated that the hepatic artery route successfully delivered BMMCs to the liver. The early improvement of laboratory indices of liver function should be interpreted with caution, because this study was not designed to evaluate efficacy. The median Model for End-Stage Liver Disease score had not deteriorated 1 year later. The occurrence of a graft-versus-host disease-like phenomenon highlights the importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 36 publications
3
53
0
Order By: Relevance
“…However, the reduced cellular immune response was usually found in the patients of alcoholic liver cirrhosis complicated with HCV [6], hence the HSCs transplantation did not result in any adverse effect related to the immune response, which has been confirmed by Couto BG [9]. Depressed cellular immune function is often shown in patients with HBV-or HCV-induced cirrhosis [11].…”
Section: Selection Of Bone Marrowmentioning
confidence: 78%
See 2 more Smart Citations
“…However, the reduced cellular immune response was usually found in the patients of alcoholic liver cirrhosis complicated with HCV [6], hence the HSCs transplantation did not result in any adverse effect related to the immune response, which has been confirmed by Couto BG [9]. Depressed cellular immune function is often shown in patients with HBV-or HCV-induced cirrhosis [11].…”
Section: Selection Of Bone Marrowmentioning
confidence: 78%
“…The type of stem cells should be selected cautiously and carefully to avoid enhancing the immune response and triggering an immune system disorder [3] [4] [8] [9]. MSCs is preferred over HSCs for the cirrhosis with the severe inflammation.…”
Section: Selection Of An Appropriate Stem Cell Typementioning
confidence: 99%
See 1 more Smart Citation
“…Whilst no studies report superior outcomes when cells are directly injected into the liver (portal vein or hepatic artery), there have been complications such as hepatic artery dissection [19] and increased portal hypertensive bleeding [20] following this approach. Furthermore, the intravenous administration of autologous BM mononuclear cells resulted in hepatic homing of the injected cells suggesting this easier, safer route may be an adequate option for cell delivery [9,21].…”
Section: Stem Cells For the Treatment Of Liver Diseasementioning
confidence: 99%
“…In models of acute liver failure, transplantation of these cells increase the survival rate [1,2]. Furthermore, recent clinical trials have demonstrated that transplantation of these cells or their fractions improves the condition of patients with cirrhosis [3][4][5], as well as improve liver function in animal models of cirrhosis [6]. Moreover, BMMC are characterized by their ability to differentiate into several functional mature cell types both in vivo and in vitro, including cardiomyocytes [7,8], endothelial cells [9], neurons [10,11] and hepatocytes [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%